Hemoglobin-to-red blood cell distribution width ratio: a new insight into cognitive protection for obese individuals - Xu, Ruikai; Wu, Zelin; Liu, Zhonghua (Frontiers in Medicine, 2025)
Background and ObjectiveAging and obesity are recognized as risk factors for cognitive decline. Hemoglobin (Hb) reflects oxygen supply capacity, while red blood cell distribution width (RDW) reflects levels of inflammation and oxidative stress. The hemoglobin-to-red blood cell distribution width ratio (HRR), by integrating the core physiological functions of Hb and RDW, can more comprehensively reflect the common mechanisms affecting aging, obesity, and cognitive function. The objective of this research was to explore the link between the HRR and cognitive performance among the obese population.MethodsThis cross-sectional study used data from the National Health and Nutrition Examination Survey (NHANES) and employed multiple regression analysis, smooth curve fitting, and subgroup analysis to investigate the relationship between HRR and cognitive function.Results1,055 obese individuals aged ≥60 years participated in the study. After adjusting for covariates, HRR was significantly positively correlated with DSST scores (β = 14.45; 95% CI, 7.55–21.35) and total cognitive Z-scores (β = 1.53; 95% CI, 0.40–2.67). HRR was significantly negatively correlated with low cognitive function as assessed by DSST (OR = 0.04; 95% CI, 0.01–0.23). Compared to individuals with lower education levels, those with higher educational backgrounds showed a more pronounced positive correlation between HRR and DSST scores.ConclusionMaintaining a higher HRR may be an important strategy for protecting cognitive function in obese individuals aged ≥60 years.